Effect of Ultrasonic Modification on the Interaction between Blueberry Pectin and Cyanidin-3-O-Glucoside - Fangjian LUO; Fengqin LU; Dajing LI; Cunshan ZHOU; Liying NIU; Lei FENG; Yayuan XU; Zhongyuan ZHANG (Shipin gongye ke-ji)
This study involved the ultrasonic modification of water-soluble pectin, chelator-soluble pectin, and sodium carbonate-soluble pectin in blueberries using different ultrasonic treatments (688, 1376, 2063 W/cm2, 10, 20, 30 min). The research explored the relationship between the modified pectin structure and the interaction between pectin and cyanidin-3-O-glucoside (C3G). The results showed that ultrasonic modification resulted in enhanced interaction between pectin and C3G. After the ultrasonic treatment of 2063 W/cm2 for 10 min, all three pectins showed the maximum binding capacity with C3G, which was about 2~6 times higher than that without the ultrasonic modification. Whereas, prolonged ultrasonic time (20~30 min) was unfavorable for the interaction between modified pectin and C3G. After ultrasonic modification, the particle size of the pectin-C3G complexes became smaller, the Zeta potential was increased, and the physical stability was thus improved. In three different pectin samples, ultrasonic treatment induced a reduction in molecular weight and methyl esterification of the pectin, facilitated the degradation of the branched structures, promoted the number of free carboxyl groups, and increased the presence of structural network voids. The alteration of the structural properties of pectin by ultrasonic treatment facilitated the interactions between pectin and C3G.